2023
DOI: 10.3390/pharmaceutics15082113
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Stimuli-Responsive Intelligent Antibacterial Nanomaterials

Abstract: Drug-resistant bacteria and infectious diseases associated with biofilms pose a significant global health threat. The integration and advancement of nanotechnology in antibacterial research offer a promising avenue to combat bacterial resistance. Nanomaterials possess numerous advantages, such as customizable designs, adjustable shapes and sizes, and the ability to synergistically utilize multiple active components, allowing for precise targeting based on specific microenvironmental variations. They serve as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 121 publications
0
3
0
Order By: Relevance
“…The results indicated that clusters of AgNPs were observed adhering to the surface of the bacterial cell walls, suggesting potential harm to the cell membranes [ 105 ]. This composite nanoparticle has been increasingly utilized as a promising and efficient antibacterial agent in recent years [ 106 ]. The addition of areca leaf extract to chitosan and chitosan/vanillin (CH/Vn) blend films has been shown to enhance the antibacterial activity of chitosan films [ 107 ].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…The results indicated that clusters of AgNPs were observed adhering to the surface of the bacterial cell walls, suggesting potential harm to the cell membranes [ 105 ]. This composite nanoparticle has been increasingly utilized as a promising and efficient antibacterial agent in recent years [ 106 ]. The addition of areca leaf extract to chitosan and chitosan/vanillin (CH/Vn) blend films has been shown to enhance the antibacterial activity of chitosan films [ 107 ].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Compared with antibiotics, nanomaterials can produce synergistic antimicrobial effects through multiple mechanisms of action and can act on specific targets within the bacterial cell, reducing the risk of resistance development [7]. Nanomaterials have the advantages of broad-spectrum antibacterials, high efficiency, and low toxicity, and can play an antibacterial role by destroying bacterial cell membranes or interfering with bacterial physiological activity [8]. For example, A.F.…”
Section: Introductionmentioning
confidence: 99%
“…and external stimuli (light, electricity, magnetic, heat, sound, etc.) that can release drugs under specific stimuli or induce collaborative antibacterial mechanisms, which has attracted great attention in biofilm research [36].…”
Section: Introductionmentioning
confidence: 99%